2019
DOI: 10.1103/physrevb.100.024107
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetism of collapsed lanthanide elements

Abstract: Using synchrotron X-ray diffraction, we show that the long-accepted monoclinic structure of the "collapsed" high-pressure phases reported in seven lanthanide elements (Nd, Tb, Gd, Dy, Ho, Er and (probably) Tm) is incorrect. In Tb, Gd, Dy, Ho, Er and Tm we show that the collapsed phases have a 16-atom orthorhombic structure (oF 16) not previously seen in the elements, while in Nd we show that it has an 8-atom orthorhombic structure (oF 8) previously reported in several actinide elements. oF 16 and oF 8 are memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 49 publications
(41 reference statements)
1
30
2
Order By: Relevance
“…The structure of Sm metal above 93 GPa is found to be face-centred orthorhombic (oF 8), iso-structural with that observed in Nd, Am, Cm and Cf at high pressures, and iso-symmetric with the oF 16 structure observed in Tb, Gd, Dy, Ho, Er and (probably) Tm 18 . High precision measurements of the compressibility of Sm reveal that it becomes less compressible after the transition to the hP 3 phase at 43 GPa, and that above 65 GPa its compressibility is that of a "regular" metal such as Au or Pt.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…The structure of Sm metal above 93 GPa is found to be face-centred orthorhombic (oF 8), iso-structural with that observed in Nd, Am, Cm and Cf at high pressures, and iso-symmetric with the oF 16 structure observed in Tb, Gd, Dy, Ho, Er and (probably) Tm 18 . High precision measurements of the compressibility of Sm reveal that it becomes less compressible after the transition to the hP 3 phase at 43 GPa, and that above 65 GPa its compressibility is that of a "regular" metal such as Au or Pt.…”
Section: Discussionmentioning
confidence: 74%
“…The compressibility of Sm to 222 GPa, including the data of Husband et al below 50 GPa 27 , is shown in Figure 7. The similarities of the hP3 and oF8 structures, which differ only in the stacking sequence of their hcplike layers 18 , results in a sizable pressure range (for example, 93-157 GPa in one of our samples -see Figure 3) over which mixed hP3-oF8 profiles are observed, and in extensive peak-overlap in this mixed-phase region. The P6 2 22 and Fddd space groups are not group-subgroup related and so the transition between the hP3 and oF8 structures need not be second order.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations